The CHF enhancement combining nano-fluid and honeycomb porous plate in a saturated pool boiling - Shoji, Mori; Mt Aznam, Suazlan; Kunito, Okuyama (American Society of Mechanical Engineers (ASME), 2014)
Several studies have proposed the use of nanofluids to enhance the in-vessel retention (IVR) capability in the severe accident management strategy implemented at certain lightwater reactors. Systems using nanofluids for IVR must be applicable to large-scale systems, i.e., infinite heated surfaces. However, the effect of the size of heater with nanoparticle deposition was revealed that the CHF is decreased with the increased heater size. On the other hand, the CHF using a honeycomb porous plate was shown experimentally to be more than twice that of a plain surface with a heated surface diameter of 30 mm, which is comparatively large compared to 10 mm. This enhancement is resulted from the capillary supply of liquid onto the heated surface and the release of vapor generated through the channels. In the present paper, in order to enhance the CHF of a large heated surface, the effects of a honeycomb porous plate and a nanofluid on the CHF were investigated experimentally. As a result, the CHF was enhanced greatly by the attachment of a honeycomb porous plate to the modified heated surface by nanoparticle deposition, even in the case of a large heated surface